Effect of thermotropic liquid crystalline poly(ether ketone)arylates on the processibility and properties of poly(ether ether ketone)s fibers. Issue 16 (6th March 2014) - Li, Ruosong; Wu, Ting; Zeng, Luxian; Xu, Jianjun; Liu, Pengqing
ABSTRACT A series of composite fibers based on poly(ether ether ketone)s (PEEK) and a thermotropic liquid crystalline poly(ether ketone)arylates (PEKAR) have been prepared by melt spinning. The structure, compatibility, and properties of these composite fibers were investigated in detail by rheological measurements, differential scanning calorimetry, thermogravimetric analysis, wide‐angle X‐ray diffraction, scanning electron microscopy, orientation degree test, and mechanical properties test. The results showed that the addition of PEKAR could reduce the apparent melt viscosity of the blends obviously, which is beneficial in improving the processibility of PEEK at a relatively low temperature. After adding 1 wt % PEKAR to PEEK, the tensile strength of the post‐treatment fiber improved by 8.8%, whereas the crystallinity of the as‐spun fiber increased from 21.76% to 31.51%, and the orientation degree also increased with the addition of PEKAR. The result of morphology research suggested that PEKAR had a good compatibility with PEEK resin. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40595.